2014
DOI: 10.1371/journal.pone.0112909
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analyses of the Spatio-Temporal Relationships of Human Medulloblastoma Subgroups during Early Human Neurogenesis

Abstract: Medulloblastoma is the most common form of malignant paediatric brain tumour and is the leading cause of childhood cancer related mortality. The four molecular subgroups of medulloblastoma that have been identified – WNT, SHH, Group 3 and Group 4 - have molecular and topographical characteristics suggestive of different cells of origin. Definitive identification of the cell(s) of origin of the medulloblastoma subgroups, particularly the poorer prognosis Group 3 and Group 4 medulloblastoma, is critical to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Evidences of a deregulated clathrin-mediated endocytosis pattern have been reported for MB group 4 during early human neurogenesis (Hooper et al, 2014), and detected in our Set B (data not shown) as well as in Set A, where a large number of deregulated genes belongs to this signaling: Rab11fip4 (Horgan and McCaffrey, 2009), Ehbp1 (Guilherme et al, 2004), Rab11fip2 (Fan et al, 2004), Zfyve20 (de Renzis et al, 2002; Naslavsky et al, 2004), Cxcl12 (Fan et al, 2004; Teicher and Fricker, 2010; Zhu et al, 2012), Sgsm2 (Yang et al, 2007), Ckap5 (Foraker et al, 2012), Vps35 (Foraker et al, 2012), and Rab18 (Foraker et al, 2012). …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Evidences of a deregulated clathrin-mediated endocytosis pattern have been reported for MB group 4 during early human neurogenesis (Hooper et al, 2014), and detected in our Set B (data not shown) as well as in Set A, where a large number of deregulated genes belongs to this signaling: Rab11fip4 (Horgan and McCaffrey, 2009), Ehbp1 (Guilherme et al, 2004), Rab11fip2 (Fan et al, 2004), Zfyve20 (de Renzis et al, 2002; Naslavsky et al, 2004), Cxcl12 (Fan et al, 2004; Teicher and Fricker, 2010; Zhu et al, 2012), Sgsm2 (Yang et al, 2007), Ckap5 (Foraker et al, 2012), Vps35 (Foraker et al, 2012), and Rab18 (Foraker et al, 2012). …”
Section: Resultsmentioning
confidence: 90%
“…In fact, a large number of deregulated genes in our Set A are also involved in the delayed differentiation of retinal cell types. Notably, it has been previously shown a parallelism between MB and retinal development; in fact, the analysis of cell populations in MB-derived from GCPs (particularly the group 3) suggests the occurrence of a potential aberrant trans-lineage differentiation into retinal neuronal precursors (Kool et al, 2008; Hooper et al, 2014). Here, given the large number of genes comprised in set A that is deregulated during the retinal cell development, we want to focus our attention on the timing of exit from the cell cycle, a crucial step in retinal cell development and differentiation, which is under the influence of Shh signaling, as it occurs in the development of MB Shh-type (Dyer, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent progress in the genomic characterization of medulloblastoma has shown that medulloblastoma is a heterogeneous disease comprised of 4 molecular subgroups: sonic hedgehog (SHH), wingless (WNT), Group 3, and Group 4 [4][5][6][7][8][9] . Signaling pathways or biological programs driving the pathogenesis of Group 3 and Group 4 subgroups have remained largely elusive [10] .…”
Section: Introductionmentioning
confidence: 99%